Association of Intrapartum CTG with Fetomaternal Outcome - Zubda Anwar, Saadia Khanam, Quddsia Tanveer, Muhammad Saqib, Anees Fatima, Mahwish Pervaiz, Bushra Meraj, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the association of intrapartum CTG with fetomaternal outcome Material and Methods: A total number of 120 pregnant females who presented in the department of obstetrics and gynecology with labour pain were included in this cross-sectional analysis. A written informed consent was taken from all patients. The study was conducted in the department of Obstetrics & Gynaecology at Islam Teaching Hospital, Sialkot from January, 2021 to September, 2021. At presentation in the labor room, 20 minutes CTG was performed and patients were divided into two groups, those having abnormal trace including suspicious and pathological trace (Group A) and normal cardiotocography (CTG) pattern (Group B). After that the patients were followed till delivery to determine the feto-maternal outcomes e.g. APGAR score, NICU admission, perinatal mortality and caesarean section rate. Results: The mean age was 26.9±4.12 years in group A and 27. 1 ± 3.9 years in group B (p-value 0.78). On comparison of maternal outcomes, caesarean section was done in 38 (63.3%) patients in group-A and in 17 (28.3%) patients in group-B (p-value <0.0001).Regarding neonatal outcomes, NICU admission was needed in 9 (15%) patients in group A, versus in 4 (6.7%) patients in group B (p-value 0.14). Perinatal mortality occurred in 03 (5.0%) patients in group A and in no patient in group B (p-value 0.07). APGAR score at 5 minutes was >7 in 46 (76.7%) patients in group A versus in 52 (86.7%) patients in group B (p-value 0.18). Conclusion: The intrapartum abnormal CTG cannot be used as the only tool to identify fetal hypoxia during labor. It may lead to increased caesarean section rate because of high false positive rate of abnormal CTG.